The interaction of (14)C-morphine with sera from immunized rabbits and from patients addicted to heroin - Hill, J. H. (1973)
An intravenous injection of morphine reduced the binding of (14)C-morphine by sera from rabbits immunized with morphine-6-hemisuccinated bovine serum albumin. Treatment of the sera with dialysis against glycine buffer (pH 3) followed by dialysis against phosphate buffered saline (PBS), conditions known to dissociate antigen–antibody complexes, restored approximately 76% of the original binding capacity. The heterogeneity of the antibody affinities was shown in both early `nonavid' and hyperimmune `avid' antisera by the demonstration of at least two distinct populations of antibodies. One population of antibodies formed loosely bonded antigen–antibody complexes and these complexes completely dissociated within 30 min. The second population had different dissociation times in the `nonavid' and `avid' antisera (15 and >72 hr respectively). The presence of the low affinity antibody resulted in different degrees of reduction of detectable binding by the standard washing procedures usually employed in the radioimmunoassay used in these studies. Washing caused less reduction in the amount of antigen bound by the more `avid' antisera. Seventy-three per cent of sixty-three serum samples from heroin addicts studied, contained opioid capable of inhibiting the binding of morphine in the radioimmunoassay employed. Methadone at concentrations likely to be present in sera did not interfere with the binding of (14)C-morphine. Sera from thirty-one of the patients were treated by dialysis against glycine buffer and PBS and then studied for the capacity to bind morphine. Only one of these thirty-one sera and none of the thirty-two sera that were not pretreated bound (14)C-morphine suggesting that an immune response to heroin is not a significant contributing factor to opioid tolerance or the development of complications, such as pulmonary oedema, following opioid administration.